Respuesta :
-1 = 5 + x/6
-6 = x/6 (multiply by 6 on both sides to cancel off the 6 on the denominator)
-36 = x
hope this helps , give brainliest
-6 = x/6 (multiply by 6 on both sides to cancel off the 6 on the denominator)
-36 = x
hope this helps , give brainliest
−1 = 5 + x6
Step 1: Simplify both sides of the equation.
−1 = 5 + x6
−1 = 5 + 16x
−1 = 16x + 5
Step 2: Flip the equation.
16x + 5 = −1
Step 3: Subtract 5 from both sides.
16x + 5−5 = −1−5
16x = −6
Step 4: Multiply both sides by 6.
6*(16x) = (6)*(−6)x = −36
Answer: x = −36
Step 1: Simplify both sides of the equation.
−1 = 5 + x6
−1 = 5 + 16x
−1 = 16x + 5
Step 2: Flip the equation.
16x + 5 = −1
Step 3: Subtract 5 from both sides.
16x + 5−5 = −1−5
16x = −6
Step 4: Multiply both sides by 6.
6*(16x) = (6)*(−6)x = −36
Answer: x = −36